Insuficiencia respiratoria aguda en paciente adulto mayor de sexo femenino de 66 años. - Batalla Santos, Karina Jesús (2020)
As of the year 2000, respiratory diseases preexisted as responsible for 10.5% of the deaths reported in our country, with a solidity of 8,287 deaths. Mortality from pectoral ailments in the adult community was 3.2 intervals higher than that examined in the child and adolescent community, with a specific rate of 54.4 deaths per 100,000 inhabitants. As part of the health personnel, I want to contribute to the orientation on the severity of acute respiratory failure in elderly patients, factors that influence the high rate of acute respiratory infections in this group of people. Therefore, this work aims to assess the severity of acute respiratory failure in a 66-year-old female elderly patient. Obtaining as a result a favorable evolution of the older adult patient suffering from acute respiratory failure, the same evolution that was thanks to the application of non-invasive ventilatory support, together with the supply of drugs to counterbalance inoculations in this recovery process. The dissemination of information inherent to the complications and severity of acute respiratory insufficiencies and the benefits of the application of non-invasive mechanical ventilation is imperative, thus generating basic knowledge among the community and promoting change of habits to promote healthy lifestyles and preventing these conditions from increasing death rates both in the elderly community and in infants.